Gorgoniapolynoe caeciliae revisited: The discovery of new species and molecular connectivity in deep-sea commensal polynoids from the Central Atlantic. (July 2022) - Maxwell, Jamie; Taboada, Sergi; Taylor, Michelle L.
Abstract: Gorgoniapolynoe caeciliae (Fauvel, 1913) is a deep-sea commensal polynoid that lives in association with several genera of octocorals from the order Alcyonacea. The species has been recorded in the Caribbean and in both Atlantic and Indian Ocean basins. The wide geographic range of G. caeciliae, coupled with it having multiple host coral species and the evolution of its taxonomic description, hints that it could potentially be a species complex. This study investigated the morphological and genetic differentiation in 82 specimens of G. cf. caeciliae, sampled from four seamounts in the Central Atlantic separated by thousands of kilometres. Our combined morphological and molecular analyses, including species delimitation models (ABGD and bPTP) using COI and a phylogenetic approach using four molecular markers ( COI, 16S, 28S, and 18S ), agreed in identifying three distinct species; two supported by morphological and molecular data and a third species, using molecular data only, from the Indian Ocean which had been previously identified as G. caeciliae. We formally describe a new species in the genus, Gorgoniapolynoe pseudocaecliae sp. nov., the most common taxa found in our study. Our morphological analyses of some members of the genus Gorgoniapolynoe revealed the presence of elytra with possible photocytes (bioluminescent cells) and conspicuous macropapillae with long cilia emerging from them, whose function is discussed here. Our demographic analysis using COI for two Gorgoniapolynoe sp. detected a high potential for dispersal for G. pseudocaecliae sp. nov., with sites approximately 3000 km apart being well connected. Unusually there was also no genetic differentiation across their bathymetric range of over 1500 m. All in all, our study highlights the importance of applying integrative taxonomy to poorly studied deep-sea species. Highlights: A large scale integrated taxonomic approach carried out on deep-sea commensal marine annelids . Molecular analysis revealed previously unknown genetic diversity within the genus Gorgoniapolynoe . Demographic analysis suggests connectivity between areas separated by thousands of kilometres, and unusually across a wide bathometric range. A new species was described based on the genetic analysis and morphological characters, Gorgoniapolynoe pseudocaeciliae sp. nov. New morphological characters for the species G. caeciliae were also revealed through scanning electron microscopy.